Development of Cemara Asri's Children-Friend Play Room - Teguh Eko Raharjo; Jaitul Anwar; Yuanita FD Sidabutar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Child-friendly Playroom which is abbreviated as RBRA is a space that accommodates children's activities to play safely, comfortably, protected from violence, not in dangerous situations and discriminatory conditions, for the sake of optimal and comprehensive continuity of children's growth and development. Children's rights to use their free time and cultural activities have a significant impact on the growth and development of children's creativity, imagination, and self-confidence, in addition to affecting children's cognitive, motoric, and socio-emotional development. Law Number 35 of 2014 which is an amendment to Law Number 23 of 2002 mandates that the State, Government, and Local Government are obliged and responsible for providing support for facilities, infrastructure, and the availability of human resources in the implementation of child protection.